PERUBAHAN SOSIAL PADA MASYARAKAT DALAM PERSPEKTIF AL-QUR`AN : (Studi Komparatif Tafsir At-Thabari) - Hasbi, Husnaini (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
The Qur'anic verse that is often presented to show the view and message of the Qur'an about social change is surah al-Ra'd (13) If you look at the opinions of scholars in understanding the meaning contained in surah Q. S. al-Ra'd (13) about the social change, there will be quite diverse opinions. As an example of the diversity of understanding the meaning of social change contained in Q.S. al-Ra'd (13) can be seen in the translation of that verse which is included in the translation of the Ministry of Religion and the translation written by M. Quraish Shihab in his book of interpretation, Tafsir al-Mishbandh. Translation of Q.S. al-Ra'd (13) as stated in the Qur'an and its translation are as follows: "Indeed, Allah does not change the condition of a people before they change their own condition”, (Al-Qur'an and its translation, 337-338). Furthermore, to be more focused and appropriate to what is being studied, the author needs to collaborate or refer to interpretations of the Al-Qur'an that relate to the topic to be studied. Thus, here is a brief explanation of how the verses of the Qur'an implement human concepts and behavior in the history of human civilization, both through the interpretations contained, including the exegesis of the book At-Thabari and the history of At-Thabari's interpretation. Research methodology is a way to find out the results of a specific problem, where the problem is also called a research problem. In Methodology, researchers use a variety of different criteria to solve existing research problems. Different sources state that the use of various types of methods is to solve problems.